2016
DOI: 10.5296/jmr.v8i4.10088
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Preferences of Leadership Style: Testing McGregor’s Theory X and Y

Abstract: In a today's ageing world, where companies are facing an increasing share of older employees, it has become essential to understand the preferences and potential of this emerging group of workers. The focus of this research is to identify the age related preferences of leadership using Theory X and Theory Y developed by Douglas McGregor. The results suggest that the majority of employees prefer Theory Y management style over the Theory X style. Regardless of the age of employees, evidence shows that the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Younger people are more focused on new approaches and they are more comfortable in case of turbulent and changing environments. Energy, intensity, and emotional expression, when operating, are characteristics of young leaders, while older leaders were more likely to maintain a modest interpersonal behaviour and to be less emotionally sensitive (Bojadjiev et al, 2016).…”
Section: Behavior Leadershipmentioning
confidence: 98%
See 1 more Smart Citation
“…Younger people are more focused on new approaches and they are more comfortable in case of turbulent and changing environments. Energy, intensity, and emotional expression, when operating, are characteristics of young leaders, while older leaders were more likely to maintain a modest interpersonal behaviour and to be less emotionally sensitive (Bojadjiev et al, 2016).…”
Section: Behavior Leadershipmentioning
confidence: 98%
“…The paper published by Robert I. Kabacoff from the Management Research Group and Ronald W. Stoffey from Kutztown University named Age Differences in Organizational Leadership, cited in Bojadjiev et al (2016), investigated the relationship between age and organizational leadership behaviour. The study showed that older leaders are more likely to study the problems in order to ensure certainty and to reduce risks, while the younger leaders are more enthusiastic to take risks, although with some reservations.…”
Section: Behavior Leadershipmentioning
confidence: 99%
“…Many studies conducted on Theory X/Y indicate that "there is no such one best organizational approach; rather, the best approach depends on the nature of the work and the organizational structure" (Hattangadi, 2015, p. 21).Besides, there is less systematic research on Theory X/Y and very few studies are being conducted to test the theory (Bojadziev et al, 2016, Gurbuz, Sahin&Koksal, 2014Kopelman et al, 20012;Shahin, 2012, Thomas &Bostrom, 2008.Conversely, McGregor's (1960) Theory X/Y on managerial assumptions are "worthwhile basis from which to examine several important individual outcomes" (Gurbuz et al, 2014(Gurbuz et al, , p. 1900, "organizational development firms continue to use assessment tools based on Theory X/Y" (Kopelman et al, 2012, p. 451) and scholars have continued to discuss and debate on theorizing it (Sahin, 2012, p. 159). Kopelman et al (2012) states that McGregor's (1960) theorizing reflects the six ideas, viz, (1) managers unknowingly makes assumptions about their employees; (2)a pessimistic view (Theory X) and more optimistic view (Theory Y) are two broad categories of managerial assumptions;…”
Section: Theory X/ymentioning
confidence: 99%
“…On the other hand, a great leader is not a great manager or vice versa and a combination of effective leadership and management counts for organizational success (Bojadziev et al, 2016). Similarly, the Theory X or Theory Y depends on the employees' industrious nature, capability and trustworthiness (Kopelman et al, 2012).…”
Section: Shanlax International Journal Of Managementmentioning
confidence: 99%